Conceptual Metaphor in SZA's Song Lyrics - Nugraheny, Amanina; Yuwita, Mia Rahmawati (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2023)
The purpose of this study is to examine how conceptual metaphors are used by SZA in her song lyrics. Finding the source domain and target domain of the conceptual metaphors used in song lyrics is the main goal of this study. A descriptive qualitative research approach is used, which includes semantic analysis and conceptual metaphor mapping in song lyrics. The information used consists of five well-known SZA songs that were specifically chosen. The author defines conceptual metaphors in 5 lyrics from SZA's song. In the “Kill Bill” song there is 1 conceptual metaphor, in the “Snooze” song there are 2 conceptual metaphors, in the “The Weekend” song there 3 conceptual metaphors, in the “Nobody Gets Me” song there are 4 conceptual metaphors, and in the “Open Arms” song there is 1 conceptual metaphor. The research provides our understanding of how conceptual metaphor is used in song lyrics and shows the depth of creativity and artistic expression found in SZA's songs. The findings of this study may be helpful for future semantics and cultural studies research, as well as for developing a deeper understanding of both the complexity and the beauty of SZA's song lyrics. Keywords: Conceptual metaphor, Lyrics, Songs, Semantics